2022
DOI: 10.1021/acsomega.2c04189
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil and Supercritical Carbon Dioxide Extract of Grapefruit Peels Formulated for Candida albicans Infections: Evaluation by an in Vitro Model to Study Fungal–Host Interactions

Abstract: Resistance to currently available antifungal agents raises the need to develop alternative remedies. Candida albicans is the most common opportunistic pathogenic fungus of humans, colonizing in the genital and intestinal mucosa, skin, and oral-nasal cavity and reducing quality of life. Herein, essential oil from grapefruit (Citrus paradise) peels was obtained by hydrodistillation, and the remaining plant material was sequentially subjected to supercritical carbon dioxide (SC-CO2) extraction to determine the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…To the best of our knowledge, the antifungal activity of the polyphenol-rich extracts obtained from GF peels against Candida albicans is reported for the first time in this study. However, a study from Yaldiz et al [99] showed that a treatment with mixtures of polyphenol-rich extracts and EO from GF peels (25:75%) for 8 h had an effective antifungal activity against C. albicans. Therefore, EOs are generally considered to be particularly effective in this context.…”
Section: Grapefruit Polyphenol-rich Extracts (Gf-ce and Gf-pe)mentioning
confidence: 99%
“…To the best of our knowledge, the antifungal activity of the polyphenol-rich extracts obtained from GF peels against Candida albicans is reported for the first time in this study. However, a study from Yaldiz et al [99] showed that a treatment with mixtures of polyphenol-rich extracts and EO from GF peels (25:75%) for 8 h had an effective antifungal activity against C. albicans. Therefore, EOs are generally considered to be particularly effective in this context.…”
Section: Grapefruit Polyphenol-rich Extracts (Gf-ce and Gf-pe)mentioning
confidence: 99%